Advances in culture, tourism and hospitality research. Vol. 1 / [Editor] Arch G Woodside - Woodside, Arch G.editor
Seeks to increase understanding and description of human behavior, conscious and unconscious meaning, and implicit/explicit decision processes applied to living and making major and everyday choices from where to live, how culture affects thinking and actions; marriage, children; work choices and behavior; leisure pursuits; and, travel behavior.